- #1

- 7

- 0

x -6 -4 -2 0 2 4 6

g(x) -4 -2 4 0 6 -6 2

Complete the table of values for the INVERSE, g^{-1}(x), in the table below:

x -6 -4 -2 0 2 4 6

g^{-1}(x)

- Thread starter andydan1056
- Start date

- #1

- 7

- 0

x -6 -4 -2 0 2 4 6

g(x) -4 -2 4 0 6 -6 2

Complete the table of values for the INVERSE, g^{-1}(x), in the table below:

x -6 -4 -2 0 2 4 6

g^{-1}(x)

- #2

ehild

Homework Helper

- 15,526

- 1,901

Consider the function g(x) represented by the table below:

x -6 -4 -2 0 2 4, 6

g(x) -4 -2 4 0 6 -6 2

Complete the table of values for the INVERSE, g^{-1}(x), in the table below:

x -6 -4 -2 0 2 4 6

g^{-1}(x)

Think of of the definition of the inverse function. If g assigns the value y to x, then g

If g(x) = -6 , x was equal to 4. So g

Can you continue?

- #3

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 956

Another way of thinking about it: g is defined by

-6 --> -4

-5 --> -2

-2 --> 4

0 --> 0

2 --> 6

4 --> -6

6 --> 2

The**inverse** function, g^{-1}, by definition, reverses that.

-6 --> -4

-5 --> -2

-2 --> 4

0 --> 0

2 --> 6

4 --> -6

6 --> 2

The

Last edited by a moderator:

- Replies
- 24

- Views
- 2K

- Last Post

- Replies
- 9

- Views
- 898

- Last Post

- Replies
- 4

- Views
- 709

- Last Post

- Replies
- 7

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 2K

- Replies
- 5

- Views
- 3K

- Last Post

- Replies
- 6

- Views
- 1K

- Last Post

- Replies
- 3

- Views
- 2K

- Replies
- 3

- Views
- 3K

- Last Post

- Replies
- 2

- Views
- 2K